Case Report: A 3’ splice site variation in RORB exon 3 associated with idiopathic generalized epilepsy in a child - Shi, Dandan; Li, Nannan; Fan, Caifang; Luo, Qiang (Frontiers in Genetics, 2025)
The RORB (Retinoic Acid Receptor-related orphan receptor β) gene plays a crucial role in neurodevelopment and is strongly associated with bipolar disorder, cognitive function, and Alzheimer’s disease. Recently, RORB has also emerged as a novel potential gene involved in generalized epilepsy and absence seizures. However, due to the complexity of RORB gene function, reports on pathogenic variations of RORB genes are still lacking. In this study, we present a case of a 5-year-old epilepsy patient. Through trio whole-exome sequencing, a heterozygous variant was identified at the splice site of 3’ end of exon 3 in the RORB gene (chr9:77249546, NM_006914.3: c.94-1G>A). This c.94-1G>A variant disrupts normal mRNA splicing, leading to the premature termination of the RORB protein. According to ACMG guidelines, this variant is classified as “likely pathogenic”. Additionally, we provide a comprehensive summary of previously reported pathogenic or likely pathogenic variants in RORB, contributing to the growing body of evidence linking this gene to epilepsy. Our findings offer valuable insights into the role of RORB in epilepsy pathogenesis, and the splice site variant identified in this study further expands the mutational spectrum of the RORB gene.